1997
DOI: 10.1080/08145857.1997.10415970
|View full text |Cite
|
Sign up to set email alerts
|

Two types of octave relationships in central Australian vocal music?

Abstract: Five performance sections from four different CentralAustralian songlines with a melodic range larger than an octave have been analysed. Although octave ratios exist, they are limited to one octave interval in each songline: only the finalis has an 'octave' counterpart, other intervals in the upper melodic range are shown to be linear shifts of intervals in the lower range. There is evidence that the octave ratio is not treated as an octave in the common musical sense (octave identity) but much more as a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Sachs ( 1962 , p. 64) noted that shrinking/expanding steps characterized Amerindian music that had no scale-wise tuned instruments. Proportional expansion of ambitus was found in Aboriginal music (Will, 1997 ). Mpyemo use scales with “mobile degrees” that are re-assigned pitch values in the process of a song (Arom, 2004 , p. 25).…”
Section: Ekmelic Modementioning
confidence: 99%
“…Sachs ( 1962 , p. 64) noted that shrinking/expanding steps characterized Amerindian music that had no scale-wise tuned instruments. Proportional expansion of ambitus was found in Aboriginal music (Will, 1997 ). Mpyemo use scales with “mobile degrees” that are re-assigned pitch values in the process of a song (Arom, 2004 , p. 25).…”
Section: Ekmelic Modementioning
confidence: 99%
“…While the octave is often reported as one of the most universal features of music [2,3,[7][8][9]85], this status has been disputed [69,[86][87][88][89]. To understand why, we review the relevant physical, statistical and perceptual ways in which the octave is considered special.…”
Section: Assessing Evidence For the Use Of The Octave By Sourcementioning
confidence: 99%
“…We wanted to examine the learning of both frequency difference and frequency ratio systems because of suggestions in psychoacoustic work that they may elicit different patterns of pitch perception (McDermott, Keebler, Micheyl, & Oxenham, 2010; McDermott & Oxenham, 2008). Some papers (Will, 1997; Will & Ellis, 1996) also suggested that frequency difference systems with ambiguous octave identity may be used in Australian aboriginal music. Including both frequency types of tuning systems could thus measure the learning of another dimension of novelty.…”
Section: Tuning Systems Examined In the Current Studymentioning
confidence: 99%